PERENCANAAN PAKET WISATA BUDAYA DI KABUPATEN TIMOR TENGAH SELATAN - Melky Kabu (Jurusan Pariwisata Politeknik Negeri Kupang, 2022)
This research uses descriptive qualitative research method with the technique of taking informants using purposive sampling technique. Data collection techniques using observation methods, library study interviews and documentation studies. The data analysis technique uses data reduction, data display and verification or drawing conclusions. The results of this study indicate that South Central Timor Regency has the potential for cultural tourism such as Benteng None, Sonaf Sonbesi and Kampung Boti. The potential for cultural tourism can be packaged into a tour package with the concept of a 2 day 1 night tour package in South Central Timor Regency. Based on the potential for cultural tourism, a tour package plan is then made at a price of Rp. 960,000 for 5 guests and a tour package packed with Culture Tour of Soe.